Picture as an Expressive Language of Early Childhood - Noorlaila M.S, Iva; Dewanti Handayani, Sri Sularti; Hartono, Hartono (Catharsis, 2019)
Language development is one of the important aspects of early childhood, language development, in essence, is a child can accept (receptive) and express (expressive). This study aims to describe the expressive language of children in Siwi Unggul Kindergarten with the media of the images he made and to analyze and describe the results of children's drawings in terms of their nature and type. This type of research is qualitative research. This research was conducted in Siwi Unggul Kindergarten, Plantungan District, Kendal Regency. The subjects of the research were Siwi Unggul Kindergarten students. The informants consisted of children, teachers, and school principals. Data collection is done by observation, interviews, and documents. The data validity technique uses triangulation. While the data analysis is done using Marshall and Rossman's interactive model, which consists of organizing data, grouping by categories, themes, and answer patterns, testing assumptions or problems that exist with the data, finding alternative explanations for the data, writing research results. The results showed that the media images created by children based on their ideas and thoughts can provoke vocabulary and expression of children's symbols (pictures and writing) in kindergarten children. Parents and teachers are expected to accompany drawing activities to stimulate children's knowledge and expressive language.